PREVALENCE OF WORKER ACCIDENTS IN ARTISAN BUSINESSES OF PANELA MACHINE, FIQUE PRODUCERS AND STONE CARVERS: Caso: Trapiches paneleros, empresas productoras de fique y talladores de piedra (2024)
ABSTRACT Introduction: There are currently three groups of workers especially exposed to suffering accidents at work due to the artisanal and informal conditions of their work, these are those dedicated to the production of panela in trapiche, the processing of fique and stone carving, trades In addition to this, it has been observed that adverse events are not reported for fear of legal consequences and job loss, which constitutes a significant and sometimes hidden risk that threatens health. and the quality of life of workers. Objective: to determine the prevalence and factors associated with the presence of occupational accidents in artisanal workers in sugar mill production, fique processing, and stone carving in the municipalities of Barichara, San Gil, Ocamonte, Curití, and Villa Nueva. Methods: A quantitative, descriptive and cross-sectional design, using a work accident test, was applied to a non-randomized sample of 90 workers who voluntarily agreed to be part of the study. Results: It was evidenced that 40% of the participants have had some type of accident, 22.2% do not use personal protection elements and 18% did not receive induction at the time of entering work, perceiving a high level of informality. in these workers that reaches 61.1% of people without ARL Conclusions: The danger that informality entails and the lack of protection elements in rural workers is undeniable, since the generation of accidents, injuries or illnesses in workers is potentially increased.